2016
DOI: 10.1111/ipd.12281
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pit‐and‐fissure sealants placed with four different bonding protocols: a randomized clinical trial

Abstract: Use of adhesives during pit-and-fissure sealant application does not significantly enhance sealant retention nor decrease marginal discoloration. Etch-and-rinse adhesive is advantageous only at short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 31 publications
(47 reference statements)
0
23
0
3
Order By: Relevance
“…A similar number of participants were enrolled in other recently performed clinical trials of the most recent generation of SE [22] and the more recent MM adhesives [2][3][4][5]8]. Controversy still remains over whether these versatile adhesives contain technological advances for overcoming the challenges associated with previous generations of adhesives or adhesion modes, since few RCTs were published and very few MM adhesives [2][3][4][5][6][7][8] have been tested in NCCL restorations [2][3][4][5]8]. Some clinical trials with different evaluation periods (18-to 36-month) tested the same MM adhesive, the Scotchbond TM Universal [2][3][4]8] applied in SE and total-etch modes for NCCL restorations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar number of participants were enrolled in other recently performed clinical trials of the most recent generation of SE [22] and the more recent MM adhesives [2][3][4][5]8]. Controversy still remains over whether these versatile adhesives contain technological advances for overcoming the challenges associated with previous generations of adhesives or adhesion modes, since few RCTs were published and very few MM adhesives [2][3][4][5][6][7][8] have been tested in NCCL restorations [2][3][4][5]8]. Some clinical trials with different evaluation periods (18-to 36-month) tested the same MM adhesive, the Scotchbond TM Universal [2][3][4]8] applied in SE and total-etch modes for NCCL restorations.…”
Section: Discussionmentioning
confidence: 99%
“…These universal systems allow for the application of the adhesive with phosphoric acid preetching, in the total-etch or ER modes, or using selective etching approaches, which enhance enamel bond durability and also provide a simplified SE mode procedure on dentine [1]. The concept behind these adhesives is novel thus only short/medium-term clinical [2][3][4][5][6][7][8] and immediate ultra-morphological and bond strength studies have been reported [9][10][11][12][13][14][15][16][17][18]. Some laboratory findings have shown that MM adhesive performance is material-dependent [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lygidakis et al reported that fissure sealants applied using an adhesive system had a higher retention rate than those that were applied without it. However, results regarding the use of an adhesive prior to fissure sealant application are conflicting . In 2015 a meta‐analysis carried out by Botton et al concluded that the nonuse of an adhesive resulted in a higher retention rate of fissure sealants in teeth without hypomineralization.…”
Section: Discussionmentioning
confidence: 99%
“…However, results regarding the use of an adhesive prior to fissure sealant application are conflicting. [83][84][85][86] In 2015 a meta-analysis carried out by Botton et al 87 concluded that the nonuse of an adhesive resulted in a higher retention rate of fissure sealants in teeth without hypomineralization. As so, further studies are needed in order to confirm the results reported by Lygidakis et al 44 Fragelli et al 41 evaluated the success of glass ionomer restorations in teeth affected with MIH, reporting a success rate of 78.8% at Comparison between groups is statistically significant at P < 0.001. c Comparison with baseline is statistically significant at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with other studies 11,15,33,34 and can be explained by the lower viscosity of the adhesive system, as compared to other materials. OptiBond FL fulfills adequately the micro porosities of enamel produced by acid conditioning 15 , forming extensions of the material (tags) 37 that favored the adhesion. On the other hand, the highest viscosity of other materials may have resulted in less wetting of surfaces of the conditioned enamel, limiting the formation of extensions to the interior of the enamel, which can justify the lowest values of adherence among them in 24 hours.…”
Section: Micro Tensile Strength Testingmentioning
confidence: 99%